Establecimiento de medidas de conservación para especies forestales en el bosque Kasama de la provincia Santo Domingo aplicando índices de biodiversidad - Franco Loor, Luis Reinaldo (2022)
This research aimed to establish conservation measures for forest species in the Kasama - Santo Domingo Forest through the application of biodiversity indices. A methodology with a qualitative approach, descriptive scope and phenomenological design was proposed. The development of the theoretical perspective was based on the review and information of bibliographic documentation and survey of forest data in the field. 32 species were identified with a total of 276 individuals, distributed in 18 families according to the six transects carried out in the 2 km2 of forest considered in the study; 8 biodiversity indices were applied, the Margalef index having the highest representativeness value within the alpha diversity; The Sorensen index obtained the best representation in beta diversity, with respect to the importance value index, they were distributed as follows, (Pholidostachys occidentalis) Palma with 53.33%, (F. benjamina L.) Matapalo with 51, 61%, (Pourouma guianensis) Mountain grape with 39.45% and (Brosimum utile) Sande with 20.01%. Regarding conservation measures, two highly necessary measures were proposed, the strengthening of a germplasm bank and the establishment of micro-nurseries